Effects of Omega-3 Co-Administered with Therapeutic Dose of lornoxicam on Male Rats’ Liver - Majeed, Israa A.; N. Al-Shawi, Nada (Iraqi Journal of Pharmaceutical Sciences, 2019)
The purpose of this study was to investigate the effect of omega-3 poly unsaturated fatty-acids co-administered with the therapeutic dose of lornoxicam on liver of healthy rats. Twenty-eight adults male rats weighing 180-200g were used in this study and the animals were randomly divided into four groups of seven rats each. Group I: negative control/rats intraperitoneally injected with normal saline in a dose 5ml/kg/day; Group II: rats intraperitoneally injected with lornoxicam at dose 0.7 mg/kg/day; Group III: rats orally-administered omega-3 only at a dose 185mg/kg/day; Group IV: rats co-administered omega-3 (185mg/kg/day) orally and intra-peritoneal injection of lornoxicam (0.7 mg/kg/day). Duration of treatment was 14-day; and at day 15 of the study, the liver of each rat was excised for the preparation of tissue-homogenate to be utilized for the estimation of ALT, AST, TNF-alpha and IL-10. Omega-3 can reduce signs of inflammation through the reduction- of TNF-alpha level and elevation of IL-10 with a significant reduction in ALT enzyme activity level in rats’ liver tissue homogenate. In conclusion, Omega-3 poly-unsaturated fatty-acids may have a protective effect against hepatocytes inflammation when co-administered with lornoxicam.